Indonesia Menghadapi Politik Liberalisasi Garam - Tanaem, ESTI R ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research aims to explain the entanglement of international relations to a province in a country through the policy of domestic salt market liberalization made by Indonesian government. Besides, this research is also give the description about domestic salt market liberalization itself which made to fulfill both the international and domestic pressures, and also the implication generated by that policy to East Nusa Tenggara. Two-level games theory will explain about the international and domestic pressures faced by the decision maker in a country. Domestic pressure will be explained by governmental process particularly about the interest groups in this domestic salt market liberalization. Furthermore, the implication to the province will be explained by concept of capitalism. Methodologically, this research uses primer and secondary data. The result of this research shows that the policy of domestic salt market liberalization was made by Indonesia government to fulfill the international and domestic pressures through some international agreements and to fulfill the domestic pressure through the different interest between bureaucrat actors and interest groups. This policy caused some implications toward potential salt producer province showed as the study case in this research, East Nusa Tenggara Province. The implication is that policy of domestic salt market liberalization marginalizes the life of salt farmers.